The Evolution of Millenarianism as a System of Historiological Views - Sołga, Przemysław (Sensus Historiae, 2021)
Millenarianism is a system of views anticipating the advent of the thousand-year Kingdom of Christ. The text accommodates the main wider historical assumptions by using the chronology from ancient to modern times. What is presented in a particularly visible manner are the thoughts of the Fathers of the Church, referring also to the sense and destiny of human history.